2010
DOI: 10.1242/jcs.063719
|View full text |Cite
|
Sign up to set email alerts
|

Non-conducting function of the Kv2.1 channel enables it to recruit vesicles for release in neuroendocrine and nerve cells

Abstract: SummaryRegulation of exocytosis by voltage-gated K + channels has classically been viewed as inhibition mediated by K + fluxes. We recently identified a new role for Kv2.1 in facilitating vesicle release from neuroendocrine cells, which is independent of K + flux. Here, we show that Kv2.1-induced facilitation of release is not restricted to neuroendocrine cells, but also occurs in the somatic-vesicle release from dorsal-root-ganglion neurons and is mediated by direct association of Kv2.1 with syntaxin. We furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 65 publications
1
42
0
Order By: Relevance
“…Transfected INS-1 b-cells were treated with GIP or GLP-1 and solubilized extracts immunoprecipitated with phosphoserine/threonine or acetyl-lysine antibodies, followed by immunoblotting with Kv2.1 antibody. GIP (1-42, 100 nM) and GLP-1 (7-36, 100 nM) increased phosphorylation (Figures 3a and b) and acetylation (Figures 3c and d) of Kv2.1, whereas truncated forms of the peptides, GIP (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and GLP-1 , that do not exhibit insulinotropic activity, had no effect. These results indicate that the incretin hormones are capable of increasing both phosphorylation and acetylation of Kv2.1 protein in pancreatic b-cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transfected INS-1 b-cells were treated with GIP or GLP-1 and solubilized extracts immunoprecipitated with phosphoserine/threonine or acetyl-lysine antibodies, followed by immunoblotting with Kv2.1 antibody. GIP (1-42, 100 nM) and GLP-1 (7-36, 100 nM) increased phosphorylation (Figures 3a and b) and acetylation (Figures 3c and d) of Kv2.1, whereas truncated forms of the peptides, GIP (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and GLP-1 , that do not exhibit insulinotropic activity, had no effect. These results indicate that the incretin hormones are capable of increasing both phosphorylation and acetylation of Kv2.1 protein in pancreatic b-cells.…”
Section: Resultsmentioning
confidence: 99%
“…12,23 Additionally, the cytoplasmic C-terminus of Kv2.1 binds to syntaxin 1A in b-cells and their interaction is involved in channel gating, trafficking and insulin exocytosis. 27,28 Multifunctional roles have also been shown in other cell types, and Kv2.1 facilitation of secretory vesicle recruitment in neuroendocrine cells, 29 and the clustering of cell surface Kv2.1 channels in hippocampal neurons 30 were shown to be independent from K þ conductance. In view of its additional pro-apoptotic role in neurons, we focused on the potential role of Kv2.1 in b-cell apoptosis and the ability of GIP and GLP-1 to modulate its action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only recently has the converse been examined, namely the question of whether this interaction controls exocytosis itself. Increasing Kv2.1 enhances exocytosis in PC12 and bovine chromaffin cells due to an interaction between the channel C-terminus (specifically, the C1a domain) and syntaxin 1A [20,22]. This effect is lost upon disruption of Kv2.1-syntaxin 1A binding, either by deletion of the C1a domain in the channel or introduction of a small peptide (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that interactions between Kv2.1 and the SNARE proteins synaptosomalassociated protein 25 (SNAP-25) [17] and syntaxin 1A [18] modulate channel electrical function. More recently, we showed that syntaxin 1A binding to a C-terminal domain of Kv2.1 directly facilitates exocytosis in PC12, bovine chromaffin and rat dorsal root ganglion cells following Kv2.1 upregulation [20][21][22], and that disruption of Kv2.1-syntaxin 1A interaction impairs noradrenaline (norepinephrine) release from permeabilised PC12 cells [23]. We therefore sought to determine whether Kv2.1 plays a direct role in insulin exocytosis as such in rodent and human beta cells.…”
Section: Introductionmentioning
confidence: 99%